Merancang Masa Depan Pendidikan: Eksplorasi Empat Kategori Kurikulum untuk Mengembangkan Potensi dan Responsivitas Sosial Peserta Didik - Mushawwir, Abdul; Kamirtang, Kamirtang; Ilyas, Hamka (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2024)
This article discusses four essential curriculum categories in contemporary education: academic subjects, humanistic, social reconstruction, and technology, each playing a crucial role in developing students' capacities. The academic subject curriculum focuses on mastering rigorous scientific content, while the humanistic curriculum prioritizes students' self-actualization according to their potential and uniqueness. The social reconstruction curriculum educates students to respond to social issues with the goal of creating a fairer and more inclusive society, and the technology curriculum prepares students with relevant skills for the digital era. This article examines how the combination of these four curricula can shape responsive and adaptive education, providing students with the tools necessary for success in an ever-changing future.